Creating memories in late 8th-century Byzantium: the short history of Nikephoros of Constantinople - Marjanović, Dragoljub (Central European medieval studies, 2018)
Creating Memories in Late 8th-Century Byzantium' is one of the key sources for our understanding of Byzantine history in the seventh and eighth century. This book offers a close look at that volume and its manner of representation of the past - Nikephoros's specific authorial method in the shaping of the image of Byzantine emperors and ecclesiastical topics linked with Iconoclasm. When seen through this lens, Creating Memories is revealed to be more engaged with and burdened by contemporary political and ecclesiastical strife than has previously been thought